Valuation of Unlisted Direct Investment Equity - Elkjaer, Thomas; Damgaard, Jannick; Kumah, Emmanuel (Washington, D.C. : International Monetary Fund, 2009)
This paper analyzes the seven valuation methods for unlisted direct investment equity included in the recently adopted IMF Balance of Payments and International Investment Position Manual, Sixth Edition (BPM6). Based on publicly available Danish data, we test the three methods that are generally applicable and find that the choice of valuation method and estimation technique can have a highly significant impact on the international investment position, pointing to the need for further harmonization. The results show that the price-to-book value method generates more robust market value estimates than the price-to-earnings method. This finding suggests that the valuation basis for the forthcoming Coordinated Direct Investment Survey - own funds at book value -will provide useful information for compiling the international investment position.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet